2022
DOI: 10.1021/acs.langmuir.2c02140
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Nonadiabatic H Atom Scattering from Low Miller Index Surfaces of Silver

Abstract: The reactivity of a surface depends strongly on the surface structure. To study the influence of surface structure on H atom adsorption, we performed inelastic scattering experiments and complementary electronically nonadiabatic molecular dynamics (MD) simulations for H atoms colliding with the three low Miller index surface facets of silver. Experiment reveals very similar energy loss distributions for all three investigated facets. However, for the (100) facet a dependence on the surface orientation is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The electronic friction is so strong in the subsurface region that the H atoms resurface within 100 femtoseconds and thermalize to the most stable binding sites. 353 Similar results were found on six metals [350][351][352] and on different surface facets, 354 suggesting the generality of the behavior originally seen for Au (111). This allowed a generalization and determination of a quantitative formula for computing the incidence angle and energy-dependent sticking probability of H and D on metals.…”
Section: H-atom Scattering From Metalssupporting
confidence: 70%
See 1 more Smart Citation
“…The electronic friction is so strong in the subsurface region that the H atoms resurface within 100 femtoseconds and thermalize to the most stable binding sites. 353 Similar results were found on six metals [350][351][352] and on different surface facets, 354 suggesting the generality of the behavior originally seen for Au (111). This allowed a generalization and determination of a quantitative formula for computing the incidence angle and energy-dependent sticking probability of H and D on metals.…”
Section: H-atom Scattering From Metalssupporting
confidence: 70%
“…5; 349 work performed with this instrument has been recently reviewed. 348 H scattering has been performed from solid surfaces composed of metals, [350][351][352][353][354][355] adsorbate-modied metals, 356 semiconductors 357,358 and graphene 359,360 grown on a number of substrates. The simplest example so far studied with this instrument is that of H scattering from a cryogenic Xe solid surface at an incidence energy of 2.76 eV.…”
Section: H-atom Scattering From Simple Surfacesmentioning
confidence: 99%
“…Electronically adiabatic potential energy surfaces are commonly used to understand the motion of chemical reactants through transition states, although it has been recognized that such treatments fail in cases where the coupling of surface adsorbate motion to electronic degrees of freedom is significant. , There are a number of well-studied examples of such systems. The sticking of hyperthermal hydrogen atoms at metal surfaces is dominated by electronically nonadiabatic dissipation of translational energy to electron–hole pairs. Diatomic molecules are known to undergo vibrational excitation or relaxation as a result of energy exchange with surface electrons. Exothermic chemical reactions can also excite electron–hole pairs, leading to macroscopic “chemicurrents” that can be observed during adsorption and recombination reactions at the surface of a metal–insulator–metal (MIM) diode …”
Section: Introductionmentioning
confidence: 99%
“…The sticking of hyperthermal hydrogen atoms at metal surfaces is dominated by electronically nonadiabatic dissipation of translational energy to electron–hole pairs. 3 7 Diatomic molecules are known to undergo vibrational excitation 8 14 or relaxation 15 21 as a result of energy exchange with surface electrons. Exothermic chemical reactions can also excite electron–hole pairs, leading to macroscopic “chemicurrents” that can be observed during adsorption and recombination reactions at the surface of a metal–insulator–metal (MIM) diode.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also confirmed the validity of MDEF in rationalizing H scattering from metals. 19,20,24 Such a theoretical framework has thus been used recently to investigate H atom scattering off H-covered tungsten surfaces, focusing both on energy transfers 23,27,28 upon scattering and Eley−Rideal and Hot-Atom recombination dynamics, 29−35 the H-Tungsten system being currently of prime interest for its implication in nuclear fusion technologies. 6,36 Previous works have shown that H-coverage increases the energy transfers and Hsticking probability at the surface.…”
Section: Introductionmentioning
confidence: 99%